Front view of the Shiva Temple 2 in the Chandrabhaga temple complex - Temples of India Project Team (Jio Institute, 2024)
The front view (east) of the Shiva Temple (Shiva Temple 2 in the Chandrabhaga temple complex), behind the Sitaleshwar Temple, shows the temple standing on a platform. The temple has depictions of the figures and deities that are associated with Shaivism. The temple has a square and plain garbhagriha (sanctum sanctorum), presently housing a Shiva linga.